PENGEMBANGAN KURIKULUM SEKOLAH DASAR UNTUK MENUMBUHKAN JIWA KEPEMIMPINAN ANAK: SYSTEMATIC LITERATURE REVIEW - Wawan Setiawardani; Rifa’atul Mahmudiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Leadership development in elementary school children is a crucial aspect of 21st-century education because it encompasses not only leadership skills but also self-management, effective communication, decision-making, and fostering social responsibility from an early age. This study aims to systematically review theliterature related to elementary school curriculum development focused on fosteringleadership in children. The method used was a Systematic Literature Review (SLR)with reference to the PRISMA 2020 protocol and the PICOC framework to formulatethe research objectives. The search process was conducted through variousinternational and national databases (Scopus, ERIC, ScienceDirect, Taylor &Francis Online, Google Scholar, DOAJ, and Garuda) with a publication range of2020–2025. Of the 1,245 articles found, only 10 articles met the inclusion criteria forfurther analysis. The results of the study indicate that emerging research themesinclude school-based leadership programs, transformational leadership, distributedleadership, service-learning, expectation-based curricula, and arts and music approaches. Curriculum development methods also vary, ranging from project-based learning, service-learning, to learning-to-lead models. The research contexts included rural elementary schools, international schools, and schools with formalleadership programs. Methodologically, experiments, large-scale surveys,phenomenological studies, systematic reviews, and mixed methods were used. Thisstudy emphasizes the importance of integrating leadership into the elementarycurriculum and opens up opportunities for further research to strengthen the